2001
DOI: 10.1023/a:1012862912259
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Charged perfect fluid with vanishing Lorentz force and massless scalar field is studied in the case of stationary cylindrically symmetric spacetime. The scalar field can depend both on radial and longitudinal coordinates. Solutions are found and classified according to scalar field gradient and magnetic field relationship. Their physical and geometrical properties are examined and discussion of particular cases, directly generalizing Gödel-type spacetimes, is presented.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Cylindrically symmetric spacetimes and their sources have belonged to useful models in classical relativity for many years. Although recently attention was paid primarily to dynamical situations in which gravitational waves are present (see, e.g., [1,2] and references therein) or to cylindrical fields motivated by string theories (e.g., [3]), unsolved questions persist even in the standard static cases.…”
Section: Introductionmentioning
confidence: 99%
“…Cylindrically symmetric spacetimes and their sources have belonged to useful models in classical relativity for many years. Although recently attention was paid primarily to dynamical situations in which gravitational waves are present (see, e.g., [1,2] and references therein) or to cylindrical fields motivated by string theories (e.g., [3]), unsolved questions persist even in the standard static cases.…”
Section: Introductionmentioning
confidence: 99%
“…The defining equations (2.1) show that in this paper the g zz metric field component is constant, in contrast to [5,7], where the case with constant g tt component was studied.…”
Section: Preliminariesmentioning
confidence: 89%
“…Kanti and Vayonakis [3] have extended analysis of [2] on case with an electromagnetic field, and their found that the chronology is violated. Also results of others authors show that presence of the electromagnetic field may cause the chronology violation (especially purely magnetic filed parallel to the rotation axis) while a scalar field may again restore the chronology [4,5].…”
Section: Introductionmentioning
confidence: 85%